The four antelope species on the Qinghai-Tibet plateau face habitat loss and redistribution to higher latitudes under climate change. (April 2021) - Zhang, Jingjie; Jiang, Feng; Li, Guangying; Qin, Wen; Wu, Tong; Xu, Feng; Hou, Yuansheng; Song, Pengfei; Cai, Zhenyuan; Zhang, Tongzuo
Highlights: The habitat of four antelopes showed a decreasing trend under climate change. The four species were predicted to migrate to higher latitudes in the future. The migration paths provide reference for the establishment of corridors. Abstract: Climate change is predicted to directly or indirectly affect species distribution and abundance, especially the species that live on the Qinghai-Tibet plateau that is highly sensitive to climate change. The Przewalski's gazelle ( Procapra przewalskii ), the Goitered gazelle ( Gazella subgutturosa ), the Tibetan gazelle ( Procapra picticaudata ) and the Tibetan antelope ( Pantholops hodgsonii ) are the only four existing antelopes living on the plateau. They play indispensable roles in regulating the structure and function of the plateau ecosystem. To understand how climate change affects the spatial distribution and migration direction of these ungulates, we applied the maximum entropy (MaxEnt) model and used 82, 57, 397 and 324 GPS points of Przewalski's gazelle, Goitered gazelle, Tibetan gazelle and Tibetan antelope, respectively. These points were mainly obtained through the survey of the line transect method and a small part from the database, and then we combined with the related environmental variables, and afterwards evaluated to predict the habitat change and shift of species geographic range under three climate scenarios in the 2050s and 2070s. Additionally, the potential migration paths in the future were simulated by the Minimal Cumulative Resistance (MCR) model. The results showed that climate change would cause habitat loss for all four species. The Tibetan antelope was predicted to lose over 50% of its current inhabited area under the most severe climate scenario. Also, the suitable habitat of all species would shift to higher latitudes. In particular, the Przewalski's gazelle as an endangered species that occupies narrow habitat area would face more severe challenges in the future. Therefore, all suitable habitats should be considered as important protection areas, and our results also provide a reference for designing the optimal migration corridors for the investigated species.